Implantação e implementação da rede de enfrentamento à violência do Município de Lajeado/TO - Oliveira, Mateus Araújo de (Universidade Federal do Tocantins, 2024)
The violence prevention network comprises a set of services and their social actors gathered in pursuit of a common goal, social protection. This network was recognized as non-static and univocal, the network presented in this work was constantly moving through communication and coordination. With that said, this work aimed to analyze the process of implementation and implementation of the violence confrontation network in Lajeado-TO, identifying the potentialities and challenges involved in this process within the capitalist mode of production. Regarding the methodological approach, the work was characterized as qualitative, documentary, and field research. The research was conducted in the municipality of Lajeado, along the TO-010 highway, between the cities of Miracema do Tocantins, Tocantínia, and Palmas. The data collection instrument was semi-structured interviews. The data were organized into analysis categories and interpreted based on history, inspired by historicaldialectical materialism and technical guidelines on networking. The internship reports from the years 2021 and 2022 were analyzed, and the interpretation was carried out based on documentary analysis.As for the results, it was understood that the implementation process of the violence confrontation network was effective in the municipality, and implementation occurred through activities such as meetings, training, and community events. However, a logic of sectoralization and individualization in services was perceived, often hindering network work, although all services were supposed to work together for identification, notification, assistance, and case studies. We understand that these obstacles and barriers in social public policies are expressions of the capitalist economic model that values individuality and fragmentation, which can contribute to the weakening of social policies. Therefore, network work becomes increasingly necessary, with intersectoral, interdisciplinary, transdisciplinary, non-hierarchical, and horizontal methodologies for confronting violence, considering the responsibility of social public policies, together with their social actors, towards users.